Entre os muros das escolas : novas configurações das rotinas e práticas escolares frente à percepção do aumento da insegurança - Gastal, Mariana (2017)
The school universe carries, quintessentially, the identity of a place of positive sociability, of ethic values apprenticeship and of critical thinking, based on dialogue and appreciation of diversity. However, when it suffers the echoes of wider social processes, such as the globalization, the post-modernity and the social controls related to them, that identity might end up fairly affected. Each day more subjected to safety devices, in the attempt to control the insecurities to which they feel exposed, educational institutions present themselves as an interesting field to perform an investigation. Thus, by means of the case studies of a municipal, a state and a private school in the city of Porto Alegre, and adopting as theoretical background David Garland’s “Culture of Control”, the research aims to find out to which extent the perception of insecurity increase can be related to the modifications suffered in each of the three. To achieve a wide and detailed knowledge of the subject, the research embraces a theoretical dimension, via bibliographic review, and an empirical one, via semi-structured interviews, questionnaires, informal dialogues and, to a lesser extent, documental analysis. The interviews and questionnaires were administered to the headmaster of the school, to members of the pedagogical team, teachers and parents. Instead of focusing the analysis on the statistical data about violence, the idea is to observe the prominence of the subjective aspects of insecurity, under the allegation that the interpretations about it interfere in the way people and institutions act. The study intends to contribute to a better understanding of the influence that those interpretations exert in the conditioning of school’s routines and experiences.